Does green credit affect enterprises’ energy efficiency? - Zhang, Chong; Zhou, Chaobo (Frontiers in Energy Research, 2023)
Whether green credit promotes heavily polluting enterprises' energy efficiency is indeed of great practical significance for China to early achieve the "double carbon" goal. This paper uses the green credit guideline issued in 2012 as a natural experiment drawing on the relevant data of Chinese listed enterprises from 2009 to 2020. It adopts a difference-in-differences model to assess the effect of green credit guideline on energy efficiency. The research finds green credit guideline improve the energy efficiency level of pilot enterprises by 0.0141 compared to non-pilot enterprises, and green credit guideline can improve energy efficiency by encouraging enterprises to increase research and development investment. Further, trade credit promotes the positive impact of green credit guideline on the energy efficiency. Moreover, green credit guideline plays a role in stimulating energy efficiency in enterprises in regions with high marketization degree, enterprises with 2 high liquidity ratio and state-owned enterprises.